A case report of a coronary artery fistula to coronary sinus with giant aneurysm: risk does not end with repair. Issue 6 (27th October 2020) - Poretti, Giulia; Lo Rito, Mauro; Varrica, Alessandro; Frigiola, Alessandro
Abstract: Background: Isolated coronary arteriovenous fistulas are extremely rare, accounting for 0.08–0.4% of all congenital heart disease. Closure of the fistula is recommended in cases of large dimensions, relevant left–right shunt, or ischaemic events. Thrombosis of the coronary aneurysms may occur as a postoperative complication. Case summary: We report a case of a coronary fistula between the circumflex artery and coronary sinus with giant aneurysm. After a failed percutaneous closure attempt, the patient was surgically treated without major postoperative complications. Despite therapeutic anticoagulation and antiplatelet therapy, she presented at clinical follow-up with thrombosis of the dilated coronary artery without signs or symptoms of ischaemia. Discussion: Management of coronary artery fistula may be challenging in cases in which initial percutaneous closure is unsuccessful. This particular case also highlights the importance of close follow-up, despite optimal therapy, to detect potentially lethal complications related to the low flow in the dilated coronary aneurysm.